Negotiations Gender Srikandi Pasoepati (Study Descriptive Kualitatif Negotiations Gender Members Srikandi Pasopati in Support of Persis Solo) - Saputro, Ridwan Taufiq, Junaedi, S. Sos., M.Si, Nur Latifah, MA (2016)
Now days, the phenomenon about sport development is not only focus on the game which has become better and more competitive. This phenomenon starts to move to see the society as the supporter of football team. One of the football supporters that were existed in Solo is Srikandi Pasoepati. This club emerged between boys supporter, but they can be well received. This research tries to know how the negotiation is done by Srikandi Pasoepati, so they can be received and exist between boys supporter as the major. Therefore, this research uses qualitative descriptive phenomenology research to explain the phenomenon easily and deeply. The result of this research can be seen from negotiation of Srikandi Pasoepati by not participate the negative activity of football supporte. Therefore, they are not only received in the society, but also have the knowledge about soccer play. Srikandi Pasoepati does not only role as a garnish of the stand, they also comfort to shout, sing, use the Persis Solo attribute, and have high loyality.